2020
DOI: 10.1016/j.isci.2020.101362
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Dopaminergic Neurons Are Secondary in COX-Deficient Locomotor Dysfunction in Drosophila

Abstract: Summary Dopaminergic (DA) neurons have been implicated as key targets in neurological disorders, notably those involving locomotor impairment, and are considered to be highly vulnerable to mitochondrial dysfunction, a common feature of such diseases. Here we investigated a Drosophila model of locomotor disorders in which functional impairment is brought about by pan-neuronal RNAi knockdown of subunit COX7A of cytochrome oxidase (COX). Despite minimal neuronal loss by apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…2F). Interestingly, targeted knockdown of COX7A in only dopaminergic neurons in flies does not have effect on motor function (Yalgin et al, 2020), so the interaction demonstrated in our work is not a simple identification of direct causal PD factors, but in combination with parkin. All the complex IV mutations we tested show interactions with parkin, rescue or enhancement (Fig.…”
Section: Discussionmentioning
confidence: 71%
“…2F). Interestingly, targeted knockdown of COX7A in only dopaminergic neurons in flies does not have effect on motor function (Yalgin et al, 2020), so the interaction demonstrated in our work is not a simple identification of direct causal PD factors, but in combination with parkin. All the complex IV mutations we tested show interactions with parkin, rescue or enhancement (Fig.…”
Section: Discussionmentioning
confidence: 71%
“…Thirty-two genes are predicted as essential genes based on the grRatio filter and experimental evidence of knockout studies. The details of essential variant genes are given in Supplementary Table S4 ([ 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 ]). Most of these genes are part of metabolic processes and energy demands of the brain.…”
Section: Resultsmentioning
confidence: 99%
“…Although these genetic transsynaptic techniques are new, they have been widely used to label synaptic partners in various Drosophila neural circuits. For example, since it was developed in 2017, trans-Tango has been used to identify postsynaptic neurons in visual circuits (Zhao et al, 2019;Keleş et al, 2020;Kiral et al, 2020;Hardcastle et al, 2021;Song et al, 2021), auditory circuits (Kim et al, 2020), olfactory circuits (Talay et al, 2017;Lerner et al, 2020), taste circuits (Talay et al, 2017;Chen et al, 2019), mechanosensory circuits (Suver et al, 2019), motor circuits (Feng et al, 2020;Yalgin et al, 2020;Buhl et al, 2021), courtship $ The transcription factor (TF) construct in BAcTrace, QF-hSNAP25-Syntaxin, is toxic and cannot be panneuronally expressed, thus a driver line is required to express it. This driver line is not necessary to be specific to presynaptic partners of neurons of interest but could label a relatively broad group of neurons.…”
Section: Applications Of Genetic Transsynaptic Toolsmentioning
confidence: 99%